Antibacterial Potential of Muntingia calabura L. Ethanol Extract Against MDR Escherichia coli - Yuri Pratiwi Utami; Saparuddin Latu; Rahmah Mustarin; Imrawati; Aditya Yudistira; Rahmatia (Postgraduate, University of Mataram, 2025)
Kersen leaves (Muntingia calabura L.) have long been utilized as a traditional medicinal plant used for headaches, antiseptics, antioxidants, antimicrobials, anti-inflammatories, anti-diabetics, and anti-tumors. This study aims to determine the antibacterial activity and the concentration at which kersen leaf extract can inhibit the growth of Multi Drug Resistant (MDR) Escherichia coli bacteria. The type of research conducted is a laboratory-scale experimental study. The kersen leaves were extracted using the maceration method with a 70% ethanol solvent. The antibacterial activity was tested using the agar diffusion method with sensitive and MDR Escherichia coli bacteria at varying concentrations of 1.25%, 2.5%, 5%, and 10%, conducted in three replicates and incubated for 24 hours. Subsequently, the inhibition zones were measured and the data were statistically processed. Based on the research results, at a concentration of 1.25%, an inhibition zone of 7.86 mm was obtained, at 2.5% concentration 9.65 mm, at 5% and 10% concentrations 11.93 mm and 13.98 mm on sensitive Escherichia coli bacteria, while on MDR Escherichia coli bacteria at a concentration of 1.25%, an inhibition zone of 6.51 mm was obtained, at 2.5% concentration 6.61 mm, at 5% and 10% concentrations 6.68 mm and 6.98 mm. These findings suggest that kersen leaf extract possesses moderate antibacterial activity against both sensitive and MDR E. coli, particularly at higher concentrations.